Prerequisites of demand shaping for transport services - Подвальна, Галина Василівна (Technology audit and production reserves, 2015)
In the article it is analyzed the transport service to the parameters of quality and price, determined the main factors influencing demand for transport services. It is conducted an analysis of the factors that determine the quality of transport services concept in the context of its consumer evaluation. It is investigated how displayed the price fluctuations of transport services on the demand for it, depending on the characteristics of the basic service. It is conducted an analysis of scientific approaches to a set of factors that actualize the need for transportation. Research is carried out to study the prerequisites of demand for transport services. On the basis of these researches it was found that the attributes that define the concept of quality transportation services are material attributes, trust and the possibility of the provider in the eyes of the customer, competence, communicativeness and customer orientation of performer, safety and availability of the services. It is proved that the impact of income and prices on the demand value for transport market is the greater, than more optional a nature of the needs in traffic and vice versa. It is determined that each individual manner outlined transport service, determined from the total mass of transportation needs, is the result of primary needs, hence the need for transport, spatial and temporal distance between the points of departure and destination specific cargo / passenger or group of cargo / passengers. The research results are important for the development of fundamental knowledge about the market of transport services. They will be useful in the further development of the theory and practice of management of transport enterprise on market principles.